2013
DOI: 10.1080/10810730.2013.829135
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Associations Between Hispanic Elderly Patients and Their Caregivers

Abstract: Knowing health literacy levels of older patients and their caregivers is important because caregivers assist patients in the administration of medications, manage daily health care tasks, and help make health services utilization decisions. The authors examined the association of health literacy levels between older Hispanic patients and their caregivers among 174 patient-caregiver dyads enrolled from 3 community clinics and 28 senior centers in San Antonio, Texas. Health literacy was measured using English an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 33 publications
2
69
0
Order By: Relevance
“…Our team has joined a group of investigators who assert that health literacy is a priority not only for patients but also for their caregivers in order for patients to achieve the most successful health outcomes 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team has joined a group of investigators who assert that health literacy is a priority not only for patients but also for their caregivers in order for patients to achieve the most successful health outcomes 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Lower health literacy has been reported among racial and ethnic minority groups 2,3 and approximately 15% of informal caregivers are Black, Hispanic or Asian 5,6 . Garcia and colleagues 5 reported that health literacy was low in approximately 30% of Hispanic informal caregivers of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the statistics of the TT population and WHO which stated more males than females received education to the primary and secondary school levels, and most of the elderly population were not educated. Garcia et al (2012) found 57.7% of elderly had been educated to the primary level and accounted for the low health literacy in this cohort. 23 The authors suggested that physicians and healthcare professionals ensure that patients understand the information communicated.…”
Section: Discussionmentioning
confidence: 75%
“…Garcia et al (2012) found 57.7% of elderly had been educated to the primary level and accounted for the low health literacy in this cohort. 23 The authors suggested that physicians and healthcare professionals ensure that patients understand the information communicated. In our study patients preferred doctors to educate them about their medicines; nevertheless, an educator role can be shared amongst healthcare personnel and government who partake in the therapeutic management of patients.…”
Section: Discussionmentioning
confidence: 75%
“…Illiteracy can be considered as a limiting factor for survival and quality of life, while it reduces the individual's ability to reflect and understand the factors surrounding him or her and minimizes the probability of satisfactory self-care behaviors. 15 In the search for details that could interfere in the practice of self-medication, it was sought to know about the correlation between living with the family or alone and their interference in this choice, where the following results were obtained: 66 (89.1%) reported living with the family and 8 (10.9%) live alone. Similar to the data from other studies 16 , 88% of the population of selfmedication elderly lived with someone.…”
Section: Methodsmentioning
confidence: 99%